The Over-the-Hill Gang Rides Again - MacCowan, George; Southcott, Fleet; Astaire, Fred; Brennan, Walter; Buchanan, Edgar (Fred Astaire's Movie Collection, 2017)
"The Over-the-Hill Gang Rides Again" starring Walter Brennan and Fred Astaire is a 1970 ABC Movie of the Week sequel to the Western comedy "The Over-the-Hill Gang". The supporting cast includes Edgar Buchanan, Andy Devine, Chill Wills, Lana Wood, and Burt Mustin (all of whom, except Wood, were in "The Over-the-Hill Gang"). Like the 1969 original, the sequel involves a group of aging Texas Rangers and was written by Richard Carr and directed by George McCowan. Pat O'Brien had played the second lead in the first film, but his character was left out of the sequel and he was effectively replaced by Astaire, who was not in the original film. This was the final film for three-time winner Academy Award-winner Walter Brennan. [wikipedia.org]